Translations from Turkish in Croatia, 1990-2010 - Ušumović, Neven (Array, 2010)
Croatia has relatively few translators from Turkish. Most of them are employed at the Chair of Turkish Studies at the Faculty of Philosophy, University of Zagreb (five persons) and approximately the same number of graduated students of Turkish has been translating occasionally from Turkish. To be sure, not all of them are equally or even nearly equally active: some of them have gained reputation by more or less continually translating Orhan Pamuk’s novels, while others engage in translation only occasionally and to a limited extent. The Chair of Turkish Studies has had the leading role in training translators from Turkish. It was founded in 1994 at the Faculty of Philosophy, and today it is part of the Department of Hungarian, Turkish, and Jewish Studies. Even though the programme includes all that is important for Turkish and Ottoman studies, including the basics of Arabic and Persian languages, its focus is on contemporary Turkish language, which is studied over the period of five years according to the Bologna system.